Fractionation of Copper in Soils Around Waste Dump site in Kaduna Municipality, Nigeria - Sanda, Sanda; R, Ahmad; Abdulrazak, Zakari H; Mohammed, Jibril (Annals of Arid Zone, 2019)
Generation of waste is increasing rapidly with increase in population, urbanization and industrialization. The indiscriminate dumping waste may cause serious environmental pollution. Copper among the other heavy metals was found as toxic accumulation at dumping sites. The bio-availability of copper (Cu) from soil could be estimated by a variety of chemical extraction procedures differing in nature and concentration of extractants, the sample weight and the time of extraction. The present study compared two different methods namely single and sequential extraction. Concentrated nitric acid (HNO3) and 0.01 mol/L acetic acid (CH3 COOH) were used as the single extractants. Whereas deionized water and varying strength of acids and alkali were used for sequential extraction of copper fractions. The total copper content ranged from 248 to 24700 mg kg-1 soil around the dump site. About 49 to 88% of the total copper was extracted using concentrated nitric acid. The results revealed that even strong acid HNO3 is unable to release the cupper tightly bound to the soil matrix. This particular method with microwave digestion is commonly used for the estimation of anthropogenic pollution. On the other hand, the lowest copper yield was obtained using the acetic acid as the single extraction agent. In this case the concentrations were below 0.16% of the total Cu contents an amount that is generally referred as bio-available to plants. Key words: Bio-availability, extraction methods, humic acid, tightly bound, anthropogenic.